Faktor-Faktor Yang Mempengaruhi Penyapihan Bayi Umur Kurang Dari 6 Bulan Melalui Studi Cross Section - Dahniar Dahniar; Nurdiana Nurdiana; Abdul Halim (ESTIMASI: Journal of Statistics and Its Application, 2021)
Weaning too early can affect the growth of the baby and the mother often ignores the nutritional needs of the baby. In addition, malnutrition is more common today than during the first 4-6 months of life. This is because many families do not understand the special needs of babies and are unable to provide food with good nutritional value. The type of research used is a survey with a cross-sectional study approach. The population is all mothers who have babies aged 6 months and the sample is all mothers who have babies aged 6 months. The sampling technique was simple random sampling. The results showed that there was a significant effect between mothers who did weaning for less than 6 months with education = 0.006. There is a significant effect between mothers who do weaning for less than 6 months with employment status = 0.008. There is a significant effect between mothers who do weaning less than 6 months with birth spacing = 0.007.